Thermodynamic properties in quantum dot nanocomposite for white light-emitted diodes - Phuc Dang Huu; Phan Xuan Le (Institute of Advanced Engineering and Science, 2022)
For a colour conversion substance, we developed a new nanocomposite containing a CdSe/CdS/ZnS red-emitted quantum dot (QD), a green-emittedd Sr2SiO4:Eu phosphorus, and silicon resins. Regarding QD concentration and ingredients, the heat increase and optic features of the nanocomposite attributable to the QD inclusion were examined. According to the findings, a modest portion of QDs added to a photon converter at the emission wavelength of QD produced a considerable degree of heat. We used 0.2 wt% QDs over an InGaN blue-emitting light-emitted diodes (LED) chip to simulate a thermal increase in a nanocomposite. Consequently, we were able to produce a white-emitted LED module featuring a good 83.2 colour rendered index, an excellent 65.86 lm W-1 brightness, and a reasonable 94 °C thermal rise. The recently founded QD-phosphorus nanocomposite transformed white-emitted LED offers a lot of possibility of modern lighting.